2016
DOI: 10.1016/j.nepr.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Workplace wellness using online learning tools in a healthcare setting

Abstract: The aim was to develop and evaluate an online learning tool for use with UK healthcare employees, healthcare educators and healthcare students, to increase knowledge of workplace wellness as an important public health issue. A 'Workplace Wellness' e-learning tool was developed and peer-reviewed by 14 topic experts. This focused on six key areas relating to workplace wellness: work-related stress, musculoskeletal disorders, diet and nutrition, physical activity, smoking and alcohol consumption. Each key area pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Knowledge about health and wellbeing at work significantly increased following exposure to the tool, which concurs with evaluations of previously developed generic tools promoting health at work (Blake and Gartshore, 2016). Further, participants reported that they would use the new knowledge to improve their health and wellbeing at work in the future.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Knowledge about health and wellbeing at work significantly increased following exposure to the tool, which concurs with evaluations of previously developed generic tools promoting health at work (Blake and Gartshore, 2016). Further, participants reported that they would use the new knowledge to improve their health and wellbeing at work in the future.…”
Section: Discussionsupporting
confidence: 80%
“…Online educational tools can increase knowledge about generic workplace health issues amongst users (Blake and Gartshore, 2016) Online packages may increase accessibility to training for employees working shifts although face-to-face training is often valued and can be preferred in individuals with low computer confidence (Blake and Gartshore, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…6,[14][15][16][17][18][19] The outcomes of these projects were successful, and hence, adoption of distance education in the field of medical health was advocated in these cases. 6,[14][15][16][17][18][19] In general, experts recommend initiating DL with an assimilation strategy that considers the pros and cons before implementation. 17,18 Still, there is a need to widen the scope of DL training, particularly in new technical procedures and complex skills.…”
Section: Discussionmentioning
confidence: 99%
“…Also, more emphasis should be laid on observing the wellness days at work and physical activity participation should be incorporated in such days. This could motivate the nurses to be active and will promote their health and reduce their risk for developing NCDs, as shown in some interventional studies assessing the effect of physical activity on the health of nurses (Blaber, 2005;Gartshore & Blake, 2014).…”
Section: Lack Of Initiativementioning
confidence: 99%